Mulheres criminosas: representações sociais sobre mulher e crime em dois jornais populares - Ricardo Moreira Pedrosa (2012)
The present work was to investigate woman are portrayed as perpetrators of crime in news of popular newspapers, seeking to describe and analyze the social representations of women and crime in these vehicles. The database of our study was constructed from the daily purchases during the period 14 July 2010 to January 31, 2011, the popular newspapers Aqui and Super Notícia, published in the city of Belo Horizonte/MG. The treatment of the news was made through a statistical analysis of textual data with the aid of the software ALCESTE. The corpore newspapers surveyed were analyzed separately. The analysis of ALCESTE in relation to the corpus of the newspaper here has generated a set of 1,596 units of context Elementary (UCEs) with potentially analyzable events, of which 1,334 (83.58%) were considered relevant for the generation of the resulting five classes: Drugs; Map of trafficking; United for the money; Family; Trademark criminals. The analysis of ALCESTE in relation to the corpus of the newspaper Super Notícia generated a set of 1,954 elementary units of context (UCEs) with potentially analyzable events, of which 1,419 (72.62%) were considered relevant for the generation of the six resulting classes: Bad motherhood ; Violent marital relations; Drugs; United for the crime; Map of crime, Trademark criminals. The results in both media vehicles surveyed were very similar classes. This similarity is an indication that the two papers describe the world of female crime from the same references. In a first level, we realize the existence of two axes in the organization of content, revealing thereby groups of classes, or constituent elements of representations linked to the differentiation between social groups. The groups of classes named Anonymous present crime as characteristic of the poor classes of society, as opposed to the axis identified as Trademark criminals, which shows the crimes committed by individuals of higher socioeconomic status as a phenomenon of an exceptional order. This association suggests the existence of a grounding in scientific knowledge claims that have been produced throughout history, whose ideas helped create the stereotype of the poor as "dangerous classes." The aspects of social representations identified in this study demonstrated the persistence of male logic ordering of social relations in urban areas. We note that the set of social representations of the woman writer of crime are based on the belief system and values of society about the differences between the sexes. Objectified as a monster or ill, the woman who aborts, commits murder or infanticide is meant against their children from the recurrence of the knowledge from the medical and psychological. In news relating to crimes committed against their partners find the objectification of women as criminal / victim. Also, we found the image of women as criminals due to the influence exercised by men. Social representations of woman author of crime proved to be supported on systems of beliefs and sexist values and scientific knowledge.